Biorefining of Walnut Shells into Polyphenol-Rich Extracts Using Ultrasound-Assisted, Enzyme-Assisted, and Pressurized Liquid Extraction Coupled with Chemometrics - Busra Acoglu Celik; Muhammed Alpgiray Celik; Laura Jūrienė; Jovita Jovaišaitė; Rita Kazernavičiūtė; Erturk Bekar; Perihan Yolci Omeroglu; Petras Rimantas Venskutonis; Senem Kamiloglu (Foods)
Walnut (Juglans regia L.) shells are valuable agro-industrial by-products rich in polyphenols. This study investigated traditional (maceration) and advanced extraction techniques—ultrasound-assisted extraction (UAE), enzyme-assisted extraction (EAE), pressurized liquid extraction (PLE), and combined ultrasound–enzyme extraction (US-EAE)—to recover bioactive compounds from walnut shells. Extraction efficiency, total phenolic content (TPC), antioxidant capacity (ABTS•+, DPPH•), and polyphenol composition were evaluated. UPLC-ESI-MS/MS identified key polyphenols including ellagic acid, 4-hydroxybenzoic acid, vanillin, taxifolin, and quercitrin. The highest TPC (5625 mg GAE/100 g dw) was found in extracts subjected to US-EAE, in which ultrasound pretreatment (200 W, 10 min) was followed by enzymatic extraction using 0.06 mL/g Viscozyme® L at pH 3.5 and 45 °C. Under the same extraction conditions, UAE alone yielded the second highest TPC (4129 mg GAE/100 g dw). The highest ABTS•+ scavenging activity (14,478 mg TE/100 g dw) and enhanced DPPH• activity (45.38 mg TE/100 g dw) were also observed in US-EAE extracts. Chemometric techniques (PCA and HCA) revealed meaningful clustering and variation patterns among methods. These findings highlight the potential of walnut shells as a sustainable source of polyphenols and demonstrate the effectiveness of innovative extraction technologies in maximizing bioactive compound recovery for potential functional applications.